Laceration of the Iliac Vein in a Patient with a Femoral Catheter for Hemodialysis - Radojica V. Stolic; Sanja P. Milojevic (International Journal of Nephrology)
Although catheters are an ideal therapeutic treatment for all patients who need hemodialysis, their placement, use may be followed by certain complications. We present a case of iliac vein lacerations in the projection of the tip of a femoral catheter for hemodialysis in a 55-year-old patient.